The Role of Artificial Intelligence and Big Data in Improving Personalization of Tourism Marketing Campaigns to Maximize Tourist Experience - Irsyad, Ziqrurrahman; Iswanto, Dedy; Istiqlal, Istiqlal (SCIENTIA: Journal of Multi Disciplinary Science, 2024)
This study aims to explore the integration of Artificial Intelligence (AI) and big data in the tourism industry to improve real-time interaction and traveler engagement on digital platforms through a Systematic Literature Review (SLR) approach. The study was conducted by selecting literature from academic databases such as Google Scholar, Scopus, and DOAJ, using keywords such as “AI,” “big data,” “tourism,” and “real-time interaction” within the time span of 2014-2024. The results showed that AI and big data significantly improved service personalization, accelerated decision-making, and increased operational efficiency in the tourism industry. Although the benefits are great, challenges in terms of data privacy, ethical use of consumer information, and shortage of skilled labor are still major barriers to implementation. This research highlights the gaps related to the integration of AI and big data alongside other technologies such as the Internet of Things (IoT) and robotics, and the importance of strategies to overcome organizational resistance to change. Future research should focus on professional skills development and solutions to data privacy challenges to accelerate the widespread adoption of these technologies in the tourism industry.